Islamic Philanthropy Unveiled: Exploring the Impact of Zakat and Waqf in Sustainability Literature Through Bibliometric and Content Analysis - Priantina, Anita; Aufa, Aufa; Mohamad Rusli, Nurhanani Aflizan (FIKRAH, 2025)
The recognition of the need to tackle sustainability concerns has grown in recent years, leading to increased worldwide attention on the Sustainable Development Goals (SDGs). The objective of this study is to examine the function of Zakat and Waqf as described in the literature on Islamic economics and finance. Google Scholar indexed articles on these themes were chosen for comprehensive coverage, including those written in Bahasa Indonesia. A total of 527 English articles and 174 Bahasa articles were chosen by employing appropriate keywords. In order to organize the debate and address the research topic, bibliometric and content analyses were performed. The results were then divided based on the language of the articles, Bahasa Indonesia and English, in order to discover any potential variations. The Harzing Publish or Perish software was utilized for data gathering, VosViewer was employed for bibliometric analysis, and Atlas.ti was utilized to facilitate content analysis. The bibliometric analysis revealed that Zakat and Waqf significantly influence the literature related to sustainability issues in Islamic economics. The content study demonstrated that Zakat and Waqf, which are firmly established in Islamic principles, make a distinctive contribution to sustainability by fostering social justice and conscientious resource utilization, aligning with the ideals of the Sustainable Development Goals.